The social world of older people - Victor, Christina R.; Scambler, Sasha Jane; Bond, John (Maidenhead, England McGraw-Hill/Open University Press, 2009)
Providing an account of loneliness and social isolation as experienced by older people living in Britain, this book considers the incidence and effects of isolation and loneliness, identifying the factors which lead to such experiences and considering potential interventions.
Introduction -- Loneliness and social isolation: issues of theory and method -- Social relations and everyday life -- Experiences of loneliness -- Social exclusion and social isolation -- Rethinking loneliness and social isolation in later life.
Includes bibliographical references and index.
Keywords: Older people -- Social conditions. -- Great Britain; Social isolation -- Great Britain